Foliar Spray of Micronutrients Alleviates Heat and Moisture Stress in Lentil (Lens culinaris Medik) Grown Under Rainfed Field Conditions - Venugopalan, Visha Kumari; Nath, Rajib; Sengupta, Kajal; Pal, Anjan K.; Banerjee, Saon; Banerjee, Purabi; Chandran, Malamal A. Sarath; Roy, Suman; Sharma, Laxmi; Hossain, Akbar; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
The coincidence of high temperature and moisture stress during reproductive stage constrains yield potential in lentil by disrupting the plant defense system. we studied the detrimental outcomes of heat and moisture stress on lentils using a foliar spray of micronutrients. We conducted field experiments on clay loam soil (Aeric Haplaquept) in eastern India during the 2018–2019 and 2019–2020 winter seasons on rainfed lentil under residual moisture. Lentil was sown on two sowing dates (November and December) to expose December sowing to higher temperature and moisture stress. Foliar sprays of boron (0.2% B), zinc (0.5% Zn), and iron (0.5% Fe) were applied individually or in combination at the pre-flowering and pod development stages. High temperatures increased malondialdehyde (MDA) content, due to membrane degradation, and reduced leaf chlorophyll content, net photosynthetic rate, stomatal conductance, water potential, and yield (kg ha–1). Various nutrients affected the growth and physiology of stressed lentil plants. The Fe+Zn treatment outperformed all other nutrient treatments in increasing POX, APX, chlorophyll content, net photosynthetic rate, stomatal conductance, water potential, seed filling duration, seed growth rate, and yield per hectare. Foliar spray of B+Fe treatment increased seed yield by 35–38% in late-sown lentil (December). In addition, these micronutrients positively impacted physiological responses under stess. The increased intensity of canopy temperature and moisture stress negatively impacted lentil responses, with the B+Fe and B+Fe+Zn treatments alleviating heat and moisture stress-induced perturbations. Moreover, exogenous nutrients also helped in improving physiochemical attributes.